مداخل قياس رأس المال الفكري محاسبيا - د. فاضل نبي عثمان (PROSPECTIVE RESEARCHES, 2023)
The recent appearance of the concept of the intellectual capital is regarded as an important economic development. The intellectual capital is concerned with the creation of the wealth at a time of increased knowledge care and technological progress. Also، the intellectual capital has the basic role in building the strategy of the change because of its knowledge and skills coped with the new premises. Accordingly, the intellectual capital is considered as a basic leader for the permanent and comprehensive development. because of its importance mentioned above، the need for thinking to measure the capital from the countenance point of view is necessary for management and investment in an effective and subjective way that is made to support the competing advantage of the firm through providing the suitable information which the traditional counting was unable to provide. The absence of the suitable information about the intellectual capital leads to its neglectfulness for a period of time. This is dangerous and acute shortage in right decisions making. There for, looking for modern syllabuses is so important in order to measure the intellectual capital from the countenance point of view and providing the needed information. As a result, this paper includes: 1. The concept of the intellectual capital. 2. Subjects of the intellectual capital. 3. The importance of the intellectual capital. 4. Problems of measuring the intellectual capital from the countenance point of view. 5. Measuring the intellectual capital from the countenance point of view.